Structural Strength Evaluation of Building Superstructure Using Response Spectrum and Time History Analysis - Aditiya, Dio; Purnomo, Dimas Aji; Sujatmiko, Heri (Fakultas Teknik Universitas Tanjungpura, 2025)
Building A of the State University Hospital (RSPTN) of Jember University, with a structural height of 22 meters, consisting of 4 floors and one roof, requires a comprehensive evaluation of seismic performance by SNI 1726:2019 and SNI 2847:2019. This study aims to assess the structural strength and seismic performance of the upper structure using Response Spectrum Analysis and Time History Analysis methods. The analysis was conducted using ETABS v22 software, with input data including architectural and structural drawings, material properties, and loading conditions. Gravity loads (dead, additional dead, and live loads) and seismic loads were applied, with dynamic analysis performed through two approaches: response spectrum analysis using site-specific parameters (SS = 0,8680, S1 = 0,3884, soil type SD), and time history analysis using spectrally matched records from the Tohoku (1999), Iwanuma (2005), and Vina Del Mar Centro (2010) earthquakes. The analysis results show that the structure